White striping prevalence and its effect on meat quality of broiler breast fillets under commercial conditions. Issue 4 (10th April 2019) - Golzar Adabi, Shahram; Demirok Soncu, Eda
Abstract: White striping (WS), characterized by white striations on the Pectoralis major muscle, is an emerging problem for the broiler industry. Thus, the impact of WS on meat quality has become a current research topic. In this context, a 2‐year follow‐up study, to reveal the prevalence of WS in broiler integrations, was undertaken. Additionally, a laboratory experiment was conducted to determine the oxidative quality during storage and the differences in proximate composition, colour and fatty acid and amino acid profiles of broiler breast fillets scored visually as normal, moderate and severe. In integrations, the WS incidence increased with increasing broiler age and more than 50% of breast fillets obtained from 32‐ to 35‐day‐old broilers and 36‐ to 39‐day‐old broilers had stripes with different scores. Lower protein and higher fat contents were measured in the moderate and severe scored fillets than the normal fillets ( p  < 0.001). Severe score stripes induced the formation of less redness on the ventral surface ( p  < 0.05) and a darker colour on the dorsal surface ( p  < 0.01). The lowest histidine, arginine and tryptophan amounts were determined in severe fillets ( p  < 0.05). Moderate and severe scored fillets were rich in polyunsaturated fatty acids implying that they were sensitive to lipid oxidation. That suggestion was further proven by the higher TBARS values. Freeze‐thawing induced the formation of carbonyl compounds, but it did not cause differences in sulphydryl groups. Briefly, we suggest that different WS scores may affect the physicochemical and oxidative quality of breast fillets; however, more studies are needed to assert an accurate and explicit judgement.